2017
DOI: 10.24247/ijmperdaug201734
|View full text |Cite
|
Sign up to set email alerts
|

CFD Simulation of Flow Past Wing Body Junction: A 3-D Approach

Abstract: Turbulence and flow disturbances occurring at the wing body junction of aircraft causes aerodynamic drag and decreases the performance. The main objective of this work is to modify the design at wing body junction by the addition of different types of fillets and strakes and see if there is any reduction from previously generated drag. The validation of the new design was simulated using CFX where Naiver Stokes equations were solved on the modified design by using suitable turbulence models. These small modifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…The effects of adding different fillets and strakes to the wing body junction on the wing performance have been studied in Mandapudi et al (2017) in which a reduction in the drag has been observed.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of adding different fillets and strakes to the wing body junction on the wing performance have been studied in Mandapudi et al (2017) in which a reduction in the drag has been observed.…”
Section: Introductionmentioning
confidence: 99%